Detection of leptospires in bovine semen by polymerase chain reaction - Heinemann, M. B.; Garcia, J. F. [UNESP]; Nunes, C. M. [UNESP]; Morais, Z. M.; Gregori, F.; Cortez, A.; Vasconcellos, S. A.; Visintin, J. A.; Richtzenhain, L. J. (Wiley, 1999)
Objective: In view of the considerable importance of venereal transmission of bovine leptospirosis, the objective of the present study was to compare the polymerase chain reaction (PCR), culture/isolation and serology to detect leptospire infection in bovine semen. Design: Blood for serologic examination and semen for bacterial culture and PCR were collected from 20 bulls at artificial insemination centres in Brazil. Each animal was sampled twice for serology. Result: Forty-five percent (9/20) of the serum samples collected showed agglutinin titers to serovar hardjo in the first sample and 25% (5/20) had agglutinin titers to serovar hardjo in the second sample. Eighty percent (16/20) of semen samples were positive by PCR. Leptospires could not be isolated from any of the semen samples examined. Conclusion: Polymerase chain reaction can be a method of great potential for the detection of leptospires at artificial insemination centres.
Keywords: Cattle; Leptospirosis; PCR; Semen; bacterium antibody; animal; animal disease; artificial insemination; blood; Brazil; cattle; cattle disease; disease transmission; female; isolation and purification; Leptospira; leptospirosis; methodology; microbiology; polymerase chain reaction; species difference; sperm; Animals; Antibodies, Bacterial; Cattle Diseases; Female; Insemination, Artificial; Polymerase Chain Reaction; Species Specificity